Genetic diversity of potentially free-living Symbiodinium in the Xisha Islands, South China Sea: Implications for the resilience of coral reefs - Zhou, Guowei; Huang, Hui; Yu, Ziniu; Dong, Zhijun; Li, Yuanchao (Aquatic ecosystem health & management, 2012)
Free-living Symbiodinium have been the focus of considerable attention among coral reef researchers because they represent a source of symbionts for both recently recruited corals and adult corals that are subject to environmental stress (e.g. climate change). We evaluated the genetic diversity of free-living Symbiodinium in seawater collected from the Xisha Islands in the South China Sea using sequence analysis of the hypervariable region of the chloroplast 23S. We sequenced a total of 267 cloned gene fragments representing Symbiodinium in clades A, B, C, D, F, and G, of which 34 were distinct types. The diversity of free-living Symbiodinium types was high at all sites. The majority of Symbiodinium sequences belonged to clade C. There was no significant difference in Symbiodinium sequence types among sites or depths. Our results highlight the high diversity of free-living Symbiodinium pools in the coral reef environment and provide a foundation for future studies of the spatiotemporal distribution of Symbiodinium. Such information is critical to understand and predict the influence of symbiotic dinoflagellates on the adaptation of their host to environmental changes.